The Burden of Chagas Disease in the Contemporary World: The RAISE Study - Antonio Luiz Pinho Ribeiro; The RAISE Study Collaborators (Ubiquity Press, 2024)
Chagas disease (ChD), a Neglected Tropical Disease, has witnessed a transformative epidemiological landscape characterized by a trend of reduction in prevalence, shifting modes of transmission, urbanization, and globalization. Historically a vector-borne disease in rural areas of Latin America, effective control measures have reduced the incidence in many countries, leading to a demographic shift where most affected individuals are now adults. However, challenges persist in regions like the Gran Chaco, and emerging oral transmission in the Amazon basin adds complexity. Urbanization and migration from rural to urban areas and to non-endemic countries, especially in Europe and the US, have redefined the disease's reach. These changing patterns contribute to uncertainties in estimating ChD prevalence, exacerbated by the lack of recent data, scarcity of surveys, and reliance on outdated models. Besides, ChD's lifelong natural history, marked by acute and chronic phases, introduces complexities in diagnosis, particularly in non-endemic regions where healthcare provider awareness is low. The temporal dissociation of infection and clinical manifestations, coupled with underreporting, has rendered ChD invisible in health statistics. Deaths attributed to ChD cardiomyopathy often go unrecognized, camouflaged under alternative causes. Understanding these challenges, the RAISE project aims to reassess the burden of ChD and ChD cardiomyopathy. The project is a collaborative effort of the World Heart Federation, Novartis Global Health, the University of Washington's Institute for Health Metrics and Evaluation, and a team of specialists coordinated by Brazil's Federal University of Minas Gerais. Employing a multidimensional strategy, the project seeks to refine estimates of ChD-related deaths, conduct systematic reviews on seroprevalence and prevalence of clinical forms, enhance existing modeling frameworks, and calculate the global economic burden, considering healthcare expenditures and service access. The RAISE project aspires to bridge knowledge gaps, raise awareness, and inform evidence-based health policies and research initiatives, positioning ChD prominently on the global health agenda.